Критерії та показники оцінювання рівнів розвиненості професійної витривалості майбутніх магістрів військового управління - Вербин, Назарій; Verbin, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проведений аналіз проблеми обґрунтування критеріїв та показників оцінювання рівнів професійно важливих якостей майбутніх магістрів військового управління. Розглянуто наукові підходи до визначення понять «критерій», «показник» та «рівень»; виявлено загальні вимоги до критеріїв та показників. У результаті аналітико-пошукової роботи нами визначено та науково обґрунтовано наступні критерії оцінювання рівнів розвиненості професійної витривалості майбутніх магістрів військового управління: ціннісно-мотиваційний, емоційно-вольовий, інтелектуальний, діяльнісно-поведінковий, та суб’єктний, які враховують зміст компонентів структури професійної витривалості офіцерів оперативно-тактичного рівня підготовки. Кожному із вказаних критеріїв було визначено властиві їм показники. Нами запропоновано оцінювати розвиненість професійної витривалості за трьома рівнями: високий, середній та низький, які у подальших дослідженнях дозволятимуть відстежувати необхідні нам характеристики та перейти слухачам на вищий рівень досягнень. The problem of substantiation of criteria and evaluation indicators of levels of professionally important qualities of future masters of military administration has been analyzed in the article. Practical experience and research analysis indicates that the selection of diagnostic tools for qualitative evaluation of professional endurance development of the officers of tactical level training remains the main problematic issue. Therefore, in-depth studies of scientific literature and contemporary psychological and educational researches have been conducted and it helped to outline a qualitative approach to determine and substantiate criteria and diagnostic apparatus. Scientific approaches to the definition of such terms as “criterion”, “indicator” and “level” were considered; general requirements to criteria were identified. As a result of analytical and research work we identified and scientifically substantiated such evaluation criteria of levels of development of professional endurance of future masters of military administration as valued motivational, emotional volitional, intellectual, behavior and subjective, which take into account the content of the components of the structure of professional endurance of officers of tactical level training. Appropriate indicators have been identified for each mentioned criteria. We proposed to assess the development of professional endurance according to three levels: high, medium and low, which will allow us to track the required specifications and move students to higher levels of achievement in our subsequent studies. The result of the determination of the criteria and indicators for evaluation of levels of professional endurance development of future masters of military administration became the basis for the conduction of experimental research.
Evaluation criteria and indicators of professional endurance development levels of future masters of military administration
Keywords: професійна витривалість; майбутні магістри військового управління; розвиток; критерії; показники; рівні; professional endurance; future masters of military administration; development; criteria; indicators; levels